Ultrasonic extraction of anthocyanins from Lycium ruthenicum Murr. and its antioxidant activity - Liu, Zenggen (Food Sci Nutr, 2020)
The ultrasonic extraction (UE) technology, possessed the advantages of effective, energy‐saving, and environmental‐friendly, was applied to extract the anthocyanin from Lycium ruthenicum (LR). The extraction parameters of UE were optimized by response surface methodology (RSM) with Box–Behnken design (BBD). Anthocyanin composition in LR fruits grown in China was systematically identified and quantified by HPLC‐ESI‐MS. The result showed that PRG was the major anthocyanin, and delphinidin, petunidin, and malvidin were the major anthocyanidins in LR fruits. There was the same anthocyanin composition of LR and great variation in anthocyanins content of LR from different areas in China. However, there was no significant difference between wild and cultivated LR in the same region. A clear separation of LR according to geographical origins was revealed by hierarchical cluster analysis (HCA) and principal component analysis (PCA), and the discrimination model for the anthocyanin concentrations were developed using these two analysis methods. Furthermore, on‐line HPLC‐DPPH assay and scavenging activity of three kinds of radicals (DPPH·, ·OH, and [Formula: see text]) in vitro were well applied to evaluate the antioxidant activity of the LR anthocyanin extract (LRAE). And its results indicated the LRAE could be a credible antioxidant agent for applications in cosmetics, food, and medicine.